Experimental verification of consistency of micro-silica glass bead thermoluminescent detectors for mixed gamma/neutron irradiation. (February 2021) - Bindu, P. Hima; Termsuk, C.; Hubbard, M.W.J.; Ley, K.; Taggart, M.P.; Lohstroh, A.
Abstract: The thermoluminescent response of micro-silica glass beads has prompted their use as dosimeters across a variety of incident ionising radiations. This work presents the latest of a campaign to investigate, and confirm, the suitability of glass beads for neutron dosimetry applications. The impressive spatial resolution coupled with the linearity of dose response over a large dynamic range makes their use especially appropriate for applications requiring high levels of sensitivity. Data has been taken within the mixed radiation field of an americium-beryllium ( 241 AmBe) source for two contrasting geometric configurations, investigating the fall-off of counts with respect to distance and the bead-to-bead variability to a uniform radiation dose from a mixed neutron/gamma radiation field. The study also considers the effect of experimental variations due to ambient light levels and the bead mounting itself. The exceptional spatial resolution previously demonstrated allows for observation of fine detail in the plot of dose versus distance from the source. Additionally, fine resolution peaks similar to those observed in previous simulations and data are observed again here. In this work, we can exclude the possibility that these response peaks are related to the source-bead distance. Highlights: Neutron sensitive micro-silica beads with 1 mm spatial resolution. Novel fixed-dose irradiation configuration. Elemental composition determined via dispersive X-ray spectroscopy.